PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEHNOLOGI INFORMASI DAN PENGENDALIAN INTERN AKUNTANSI TERHADAP KETERANDALAN PELAPORAN KEUANGAN PEMERINTAH DAERAH - Darwanis Darwanis; Desi Dwi Mahyani (Program Magister Akuntansi Unsyiah, 2009)
This purpose of this research was to examine the effect of human resource capacity, utilization of information technology and accounting internal control toward financial reporting of local governments. The population in this study are all SKPA (Aceh Devices Unit) in Nanggroe Aceh Darussalam which amounts to 37 agencies. The data used are primary data, which derives directly from research subjects in the form of the perception of respondents with a list of how to distribute the statement in the form of questionnaires to 111 respondents.The results show that simultaneously, the capacity of human resources, utilization of information technology and accounting internal controls affect the reliability of financial reporting of local government. Partially, each independent variable influence the reliability of financial reporting of local government. Keyword: human resources, information technology, internal controls, reliability of financial reporting.